Delta-8-THC association with psychosis: A case report with literature review - Miller, Chelsea R.; Burk, Bradley G.; Fargason, Rachel E.; Birur, Badari (Frontiers in Psychiatry, 2023)
Background: Cannabis (Δ9-THC) is the most consumed illicit drug. The Agricultural Improvement Act of 2018 removed hemp, a strain of Cannabis sativa, as a controlled substance. This law allowed for the plant to be processed into its components as long as these products contain less than 0.3% Δ9-THC. As a result, a legal psychoactive substance, Delta-8-Tetrahydrocannabinol (Δ8-THC), emerged in popularity in late 2020 and is readily available and on display in stores. An increasing number of patients admitted for psychiatric hospitalization report use, with limited literature on the effects. Case Presentations: This case report describes three individual cases of patients who required admission to a university psychiatric hospital after regular use solely of Δ8-THC. All three patients developed psychotic and paranoid symptoms concurrently with the use of Δ8-THC and a severity exceeding their previous historical presentations. The presenting psychotic symptoms were also atypical for all three patients. New-onset violence and visual hallucinations were noted in two of the patients, one patient with no previous psychiatric history and one patient while on a therapeutic dose of his antipsychotic. In the third case, new onset of bizarre, fixed delusions of puppies dissolving in the bathtub developed. Conclusions: A strong body of evidence correlates the use of Δ9-THC with psychosis. Based on limited studies and increasing reports of temporal association between Δ8-THC use and the development of psychotic symptoms, it appears Δ8-THC may act at both the cannabinoid CB1 and CB2 receptors and have similar adverse psychiatric effects as Δ9-THC. Physicians should be prepared to gather a specific history of Δ8-THC use (which may be considered by patients harmless) and treat patients with Δ8-THC-related intoxication and symptoms.